Experimental Study on the Concrete with Compound Admixture of Iron Tailings and Slag Powder under Low Cement Clinker System - Ruidong Wu; Juanhong Liu (Advances in Materials Science and Engineering)
In order to study the performance of concrete with compound admixture of iron tailings and slag powder under low cement clinker system, the mixture ratio of different iron tailings powder and slag powder was designed to prepare C30 and C50 concrete. The workability, strength, carbonation depth, chloride diffusion coefficient, scanning electron microscopy (SEM), energy dispersive spectroscopy (EDS), and X-ray diffraction (XRD) of concrete were measured, respectively. The test results show that iron tailings powder is beneficial to improve the workability, and the strength of concrete decreases with the increase of iron tailings powder content, while the carbonation depth and chloride diffusion coefficient increase with the increase of iron tailings powder content. Under low cement clinker system, the iron tailings powder should not be used alone (below 70% of mineral admixture). When the ratio of iron tailings to slag powder is 1 : 1, the strength, carbonation depth, chloride ion permeation coefficient, and the microstructure of concrete are roughly the same to that of concrete with single slag powder. So, the iron tailings powder can replace S95 grade slag powder in the same quantity. Iron tailings powder does not take part in hydration reaction, but it can improve particle gradation, reach close accumulation, and increase the quantity of central grains.